The Implementasi Strategi Marketing Kue Tradisional Pojok Rumah Nyai Palembang Melalui Media Sosial - Siti Komariah Hildayanti; Juhaini Alie (Madani: Jurnal Pengabdian Ilmiah, 2022)
This Community Service (PkM) aims to implement a social media marketing plan for traditional Palembang cakes from Pojok Rumah Nyai. The (PkM) used contextual methods, discussions, and practices in executing activities. The contextual technique provided participants with content and theory initially. The discussion method consisted of a dialogue between the presenter and the participants regarding their knowledge and understanding of social media as a marketing technique. The activity participants, with the assistance of the presenters, constructed social media for their businesses and implemented social media marketing techniques. Based on the outcomes of this service, it could be determined that it offered a wealth of managerial and legal knowledge. The use of technology in the implementation of marketing operations could assist MSME owners in expanding their product sales. Using social media as a marketing tactic was one of them.